2018
DOI: 10.1016/j.theriogenology.2018.02.013
|View full text |Cite
|
Sign up to set email alerts
|

SNP rs403212791 in exon 2 of the MTNR1A gene is associated with reproductive seasonality in the Rasa aragonesa sheep breed

Abstract: The aim of this study was to characterize and identify causative SNPs in the MTNR1A gene responsible for the reproductive seasonality traits in the Rasa aragonesa sheep breed. A total of 290 ewes (155, 84 and 51 mature, young and ewe lambs, respectively) from one flock were controlled from January to August. The following three reproductive seasonality traits were considered: the total days of anoestrus (TDA) and the progesterone cycling months (P4CM); both ovarian function seasonality traits based on blood pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 24 publications
3
25
0
Order By: Relevance
“…In the present study, we firstly carried out polymorphism detection in exon 2, the most widely studied exon of MTNR1A , and found five SNPs in sheep, each locus contained three genotypes (Figure ), and both g.15118664G > T and g.15118683C > T loci were involved in amino acid changes (Figure b). Interestingly, three of the five loci had been detected in Altay sheep and Hu sheep (Wang, Shi, et al, ), and the other two loci were also found in the Rasa Aragonesa sheep (Calvo et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In the present study, we firstly carried out polymorphism detection in exon 2, the most widely studied exon of MTNR1A , and found five SNPs in sheep, each locus contained three genotypes (Figure ), and both g.15118664G > T and g.15118683C > T loci were involved in amino acid changes (Figure b). Interestingly, three of the five loci had been detected in Altay sheep and Hu sheep (Wang, Shi, et al, ), and the other two loci were also found in the Rasa Aragonesa sheep (Calvo et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Polymorphisms of MTNR1A gene have a great influence on the reproduction of goat (Carcangiu, Vacca, et al, ; Chu et al, ), cattle (Elraey et al, ), pig (Ramírez et al, ), goose (Alsiddig et al, ), buffalo (Gunwant et al, ; Jiang et al, ), chicken (Sundaresan et al, ) and sheep (Pelletier et al, , Chu, Ji, & Chen, , Chu et al, , Chu et al, , Mateescu et al, , Wang, , Lei, Di, Liu, & Chu, , Giantsis et al, , Calvo et al, ). The earliest researchers found two polymorphic loci in the 824bp of exon 2 of the MTNR1A gene in many sheep breeds using restriction endonucleases MnlI and RsaI (Messer et al, ; Notter, Cockett, & Hadfield, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Melatonin is a vital hormone that is secreted mainly by the pineal gland, and has a significant effect on several physiological functions including circadian rhythm and reproduction through binding its special receptors in mammals (Calvo et al., 2018; Chu et al., 2007; Chu, Ji, & Chen, 2003; Hardeland, 2017; Lei, Di, Liu, & Chu, 2015; Li et al., 2013; Ramírez et al., 2009) and birds (Alsiddig et al., 2016; Amit Kumar & Vinod, 2014; Feng et al., 2018; Rajesh & Chandana, 2011; Zhao et al., 2014). There are three melatonin receptor subtypes, melatonin receptor 1A (MTNR1A, MT1), melatonin receptor 1B (MTNR1B, MT2) and melatonin receptor 1C (MTNR1C), which belong to the superfamily of G protein‐coupled receptors (Dubocovich & Markowska, 2005; Reiter, 1980).…”
Section: Introductionmentioning
confidence: 99%